PERBANDINGAN HASIL BELAJAR IPA ANTARA MODEL PROBLEM BASED LEARNING (PBL) DAN MODEL KONVENSIONAL PADA SISWA KELAS V SD MUHAMMADIYAH TEMBILAHAN - M. Anas Nazarsyah Rahmatullah; Muhammad Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to compare the science learning outcomes of fifth-grade students at Muhammadiyah Tembilahan Elementary School (SD Muhammadiyah Tembilahan). This study employed a quantitative approach with a quasiexperimental nonequivalent control group design. The sample consisted of two classes: an experimental class implementing the PBL model and a control class using the conventional model. Data collection was conducted using a multiplechoice science learning outcome test, the validity and reliability of which were tested. Data analysis used normality tests, homogeneity tests, and independent sample t-tests. The results showed a significant difference between the science learning outcomes of students taught using the PBL model and those taught using the conventional model. The average learning outcome score of the experimental class was higher than that of the control class. Therefore, it can be concluded that the Problem-Based Learning model is more effective in improving fifth-grade students' science learning outcomes at SD Muhammadiyah Tembilahan compared to the conventional learning model.